Cartografia escolar, inteligências múltiplas e neurociências no ensino fundamental: a mediação (geo)tecnológica e multimodal no ensino de geografia - Rizzatti, Maurício (2022)
The relationship between School Cartography, Multiple Intelligences, Multimodality and Neurosciences is very relevant to the current context, as it helps to understand how the learning process occurs and how to think about different activities highlighting cartographic and central concepts for the teaching of Geography. Based on these premises, this work aims to study the contribution of the Theory of Multiple Intelligences and Neurosciences from the use of (Geo)Technologies and multimodal resources in the construction of geographic and cartographic knowledges in Elementary School. The theoretical foundation is organized into three chapters, covering the historical development of Cartography, Thematic Cartography, curricular guidelines, active methodologies and Multimodality, besides the historical conception of intelligences and the Theory of Multiple Intelligences. The research method is the inductive one with a quali-quantitative approach, considering the discussion of subjective elements regarding learning, as well as the quantification of the data collected to support the discussion. A didactic sequence was carried out in classes 71 and 72 of the Vicente Farencena Municipal Elementary School, located in Santa Maria, Rio Grande do Sul, using questionnaires to assess the students' preliminary knowledge, another one after the workshop to analyze the learning of the participants. Two months after the end of the activities, the students answered the third questionnaire with the aim of understanding the consolidation of memory about the themes addressed. In addition, participants were asked to answer some questionnaires about their daily activities, carried out during the night shift of the day when some activity in the didactic sequence took place, and also about the use of electronic devices before bed and the duration of sleep. The activities started with the pedagogical workshop, which presented fundamental theoretical concepts for mapping practices. This activity was carried out synchronously in class 71, on Google Meet, while in class 72, the “Remote Flipped Classroom” was implemented, with videos on contextualized themes. Afterwards, manual and digital maps on land use and occupation and sociodemographic variables of Santa Maria were made, as well as an activity highlighting the principles of mapping with a compass. The didactic sequence demonstrated that the students assimilated the worked concepts, with outliers, however, which were analyzed in the light of the students' daily activities. This allowed us to identify possible patterns that collaborate or not with learning. However, as they are individuals endowed with subjectivity, there may be variations in the data collected. Furthermore, the concept of Multi(Geo)Modal School Cartography was proposed, which synthesizes the observations of the workshop's methodological proposal, involving the intersection of School Cartography, Multiple Intelligences, Multimodality and Neurosciences, and dealing with the central concept of this Thesis.